2011
DOI: 10.1111/j.1600-079x.2011.00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Content of melatonin and other antioxidants in grape‐related foodstuffs: measurement using a MEPS‐HPLC‐F method

Abstract: The strong antioxidant activity of melatonin is well known and it is important to investigate its presence and levels in different foodstuffs, for the purpose of evaluating their nutraceutical properties. As a contribution towards this goal, an original analytical method has been developed for the simultaneous determination of melatonin and other indolic and phenolic antioxidants (including trans- and cis-resveratrol, ferulic acid, tryptophan, serotonin and 5-hydroxyindoleacetic acid) in grape-related foodstuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 35 publications
5
66
0
5
Order By: Relevance
“…Melatonin is not unique to vertebrates but is also produced in invertebrates, unicells, and plants, none of which possess a pineal gland and some of which, i.e., unicells, have no organs whatsoever (37,50,51). These nonvertebrates need melatonin for some of the same reasons vertebrates do, e.g., as an antioxidant (37).…”
Section: Unconventional Aspects Of the Pineal And Melatoninmentioning
confidence: 98%
See 1 more Smart Citation
“…Melatonin is not unique to vertebrates but is also produced in invertebrates, unicells, and plants, none of which possess a pineal gland and some of which, i.e., unicells, have no organs whatsoever (37,50,51). These nonvertebrates need melatonin for some of the same reasons vertebrates do, e.g., as an antioxidant (37).…”
Section: Unconventional Aspects Of the Pineal And Melatoninmentioning
confidence: 98%
“…Melatonin is not unique to vertebrates but is also produced in invertebrates, unicells, and plants, none of which possess a pineal gland and some of which, i.e., unicells, have no organs whatsoever (37,50,51). These nonvertebrates need melatonin for some of the same reasons vertebrates do, e.g., as an antioxidant (37). Some plants already have been genetically engineered to produce elevated quantities of melatonin, which protects them from free radical-producing environmental stressors (temperature extremes, drought, disease) (8,9).…”
Section: Unconventional Aspects Of the Pineal And Melatoninmentioning
confidence: 99%
“…Stilbenoids are generally determined by liquid chromatography (LC) using different detection systems, such as UV [11][12][13][14], fluorescence [15][16][17] or mass spectrometry [11,[18][19][20]. Gas chromatography (GC), especially when it is hyphenated with mass spectrometry (MS), has important advantages over LC, allowing identification and confirmation even at low…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have previously reported that melatonin was clearly separable from other potentially interfering indoleamines with HPLC-FD [15][16][17][18][19][20]. The extraction/purification step with solid phase extraction (SPE) further reduced the likelihood of interfering compounds.…”
Section: Melatonin Analysis By Hplcmentioning
confidence: 99%